Neurobiological Bases of Autism Spectrum Disorders and Implications for Early Intervention: A Brief Overview - Petinou, Kakia; Minaidou, Despo (My University, 2017)
Objectives: To better understand the pathogenesis of autism spectrum disorder (ASD) and implications for intervention, the current paper reports on research related to the neurobiological underpinnings of ASD and the implication for early intervention with a focus on the importance of joint attention and eye gaze behaviors. Participants and Methods: An overview is provided on the available research findings from the fields of social neuroscience and experimental psychology specific to brain development, brain pathology, eye gaze, and joint attention behaviors. Results: The results of the review converge towards the existence of aberrant brain connections and atypical brain morphology areas, which in complex and dynamic ways hinder the prioritization of social information. Consequently, the atypical social interaction skills exhibited by infants at risk for developing ASD are traced in the malformation of respective brain connections. Conclusions: Given the importance of neurobiological findings and their mapping onto early social pragmatic skills, early intervention goals need to focus on increasing appropriate eye gaze skills and joint attention. Such goals could potentially improve intervention outcomes in terms of improving social communication skills in youngsters with ASD.
Keywords: Neurobiology; Autism spectrum disorder; Joint attention; Eye gaze; Early intervention